The relationship between selected physiological variables of rowers and rowing performance as determined by a 2000 m ergometer test - Cosgrove, M. J.; Wilson, J.; Watt, D.; Grant, S. F. (Journal of Sports Sciences, 1999)
The aim of this study was to establish the relationship between selected physiological variables of rowers and rowing performance as determined by a 2000 m time-trial on a Concept II Model B rowing ergometer. The participants were 13 male club tandard oarsmen. Their mean (+/- s) age, body mass and height were 9.9 +/- 0.6 years, 73.1 +/- 6.6 kg and 180.5 +/- 4.6 cm respectively. The participants were tested on the rowing ergometer to determine their maximal oxygen uptake (VO2max ), rowing economy, predicted velocity at VO2max, velocity and VO2 at the lactate threshold, and their velocity and VO2 at a blood lactate concentration of 4 mmol.l-1. Percent body fat was estimated using the skinfold method. The velocity for the 2000 m performance test and the predicted velocities at the lactate threshold, at a blood lactate concentration of 4 mmol.l-1 and at VO2max were 4.7 +/-0.2, 3.9 +/- 0.2, 4.2 +/- 0.2 and 4.6 +/- 0.2 m.s-1 respectively. A repeated-measures anal ysis of variance showed that the three predicted velocities were all significantly different from each other (P < 0.05). The VO2max and lean body mass showed the highest correlation with the velocity for the 2000 m time-trial (r = 0.85). A stepwise multiple regression showed that VO2max was the best single predictor of the velocity for the 2000 m time-trial; a model incorporating VO2max explained 72% of the variability in 2000 m rowing performance. Our esults suggest that rowers should devote time to the improvement of VO2max and lean body mass.